Sinergi Pembinaan Dan Pengawasan: Kunci Keberhasilan Pemerintahan Daerah Kabupaten Purwakarta Dalam Konteks Reformasi Birokrasi Evaluasi Kinerja Oleh Inspektorat Daerah Kabupaten Purwakarta - Faqih Ragi; Andhika Rendra Nugraha; Adinda Putri Maharani; Nurlistiadewi K.Affandi; Ivan Darmawan (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
Bureaucratic reform is a crucial agenda in improving the performance of regional government. This research aims to analyze the synergy of coaching and supervision as the key to the success of the Purwakarta Regency government in the context of bureaucratic reform, with a focus on performance evaluation by the Regional Inspectorate. The research method uses a descriptive qualitative approach, including literature study and analysis of the Purwakarta Regency Regional Inspectorate Bureaucratic Reform Road Map document. Data were analyzed using thematic analysis techniques, focusing on eight areas of change in bureaucratic reform. The research results show that the Regional Inspectorate has implemented innovative programs within the reform framework, but faces challenges such as resistance to change and limited resources. The synergy between the coaching and supervision functions has been proven to contribute positively to improving governance and public services. In conclusion, the continuity of implementation of the road map and the role of the Inspectorate as a catalyst for change are very important for the success of reform. This research contributes to understanding the dynamics of bureaucratic reform at the district level and highlights the importance of strengthening the capacity of Regional Inspectorates in driving systemic change.